Passions and projections themes from the philosophy of Simon Blackburn - Johnson, Robert N.; Smith, Michael 1954 July 23- (Oxford University Press, 2015)
Best known to the general public for his attempts to make philosophy accessible to those with little or no formal training, Simon Blackburn's reputation in academic circles is based on a lifetime pursuit of a projectivist and anti-realist research programme in the spirit of the great David Hume. This volume of critical essays by some of the most influential philosophers working today documents the whole range and influence of Blackburn's work, and poses some novel challenges for him
Keywords: Blackburn, Simon / 1944-; Blackburn, Simon -- 1944-; Pragmatism; Philosophie; Aufsatzsammlung